Responding to Elite Consolidation: the Anti-Cement-Factory Movement Resisting Oligarchy in an Indonesian Local Election - Arif Novianto; Anindya Dessi Wulansari (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
This study demonstrates resistance to oligarchic forces with a case study from Pati Regency, Central Java, Indonesia. The movement started with a protest against the expansion of the internationally financed Indocement Tunggal Prakarsa Ltd in the Kendeng Mountains. The anti-cement-factory movement lived on and ‘defeated’ the oligarchs in the electoral districts where the movement happened in the 2017 Pati local election. This study uses a qualitative method. Data were collected from in-depth interviews between December 2016 and July 2017 with 16 social movement leaders and three regional leader’s election campaign team members. The findings show that oligarchy as a power relation system can be challenged, putting into question the belief that oligarchy as a power relation system in democracy is unchallenged. This case study in Pati Regency has shown that resistance on the grassroots level, albeit sporadic, was able to challenge the oligarchy.